Efficacy of Ketoconazole in Hormone Refractory Prostate Cancer Patients (Journal of Medicine, 2009)
Prostate cancer is a common malignancy among males, with the incidence steadily rising over the past years. Patients with small volume metastasis where early chemotherapy is not warranted, in patients with biochemical failure, and in patients who refuse chemotherapy, management remains controversial as there is no universally accepted treatment protocol. Ketoconazole is an antimycotic that inhibits cytochrome P450 enzymes that are required for the synthesis of androgens and other steroids. In addition, in-vitro studies have suggested some direct cytotoxic effects in prostate cancer cell lines. This study aims to describe our experience with ketoconazole treatment for hormone refractory prostate cancer (HRPC) at our centre. Retrospective chart review of HRPC patients given ketoconazole at a private oncology centre in Dhaka from 2005 - 2006 was done. Patients had histologically proven adenocarcinoma of the prostate with rising Prostate Specific Antigen (PSA) despite androgen deprivation therapy (ADT) with orchiectomy, LHRH agonist therapy and antiandrogens. Ketoconazole was given at 200 mg thrice daily. A total of 10 patients with HRPC was treated and evaluated for response and toxicity. Median age was 70 years old.4 (40%) of the 10 patients had a greater than 50% decrease of PSA values. Responses were seen in 66.66% (2/3) of patients with bone-only disease, 20 % (1/5) of patients with bone and soft tissue disease and 1 patient with PSA-only disease. Median duration of response was 6.75 months (range 2-14 months).There were no grade 3 or 4 toxicities. Overall, 5 (50%) patients had toxicity related to ketoconazole. Its good toxicity profile, low cost and ease of administration makes it a viable option to this group of patients specially in our country. Keyword: Prostate cancer, hormone refractory prostate cancer, ketoconazole   doi: 10.3329/jom.v10i2.2814 J MEDICINE 2009; 10 : 52-55